Analysis of Suspension System for 3D Printed Mobile Robot - Hilmi Saygın SUCUOĞLU; Ismail BOGREKCI; Pinar DEMIRCIOGLU; Ogulcan TURHANLAR (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, 3D printed mobile robot with suspension system was analysed using Computer Aided Engineering (CAE) methods. Spring and damping coefficients of the suspension system were determined. Structural and dynamic analyses were conducted after the selection of appropriate spring and damping coefficients to find structural strength and power requirement of mobile robot. The length of robot and the number of wheels were decreased to one third of the real to ease the analysis. A concrete road with the length of 1,000 mm and 10° inclination was created as ground to simulate the real world. Obstacles with the height of 80 mm were placed on different locations on the path of the wheels for the robot. The designed suspension system was consisted of; two dashpots connected to wheels and body through connection components and a spring between two wheels to ensure the stability. Polylactic acid (PLA) was used as body material.  In the structural part; the strength of the robot body and critical part (suspension leg) was computed by Finite Element Analysis (FEA). Safety factor values for body and critical component were found as almost 7 and 4, respectively. The results from the analysed indicated that maximum equivalent stresses and strains (for body = 3.4 MPa,  = 3 e-3 mm/mm and for critical component = 6.5 MPa,  = 6 e-3 mm/mm) were occurred while robot was passing the obstacles.  In dynamic analysis; robot was driven with three different speeds (0.25, 0.5 and 1 metre per second) on the same road conditions.  The motor torque and force values, suspension system results (force and elongation), angular velocity of the wheels and power requirement of mobile robot were calculated. The results showed the power requirement of robot was 70 Watt when it was driven with maximum velocity.